The effect of repeat feeding on dengue virus transmission potential in Wolbachia-infected Aedes aegypti following extended egg quiescence. - Meng-Jia Lau; Andrés R Valdez; Matthew J Jones; Igor Aranson; Ary A Hoffmann; Elizabeth A McGraw (Public Library of Science (PLoS), 2024)
As Wolbachia pipientis is more widely being released into field populations of Aedes aegypti for disease control, the ability to select the appropriate strain for differing environments is increasingly important. A previous study revealed that longer-term quiescence in the egg phase reduced the fertility of mosquitoes, especially those harboring the wAlbB Wolbachia strain. This infertility was also associated with a greater biting rate. Here, we attempt to quantify the effect of this heightened biting behavior on the transmission potential of the dengue virus using a combination of assays for fitness, probing behavior, and vector competence, allowing repeat feeding, and incorporate these effects in a model of R0. We show that Wolbachia-infected infertile mosquitoes are more interested in feeding almost immediately after an initial blood meal relative to wild type and Wolbachia-infected fertile mosquitoes and that these differences continue for up to 8 days over the period we measured. As a result, the infertile Wolbachia mosquitoes have higher virus prevalence and loads than Wolbachia-fertile mosquitoes. We saw limited evidence of Wolbachia-mediated blocking in the disseminated tissue (legs) in terms of prevalence but did see reduced viral loads. Using a previously published estimate of the extrinsic incubation period, we demonstrate that the effect of repeat feeding/infertility is insufficient to overcome the effects of Wolbachia-mediated blocking on R0. These estimates are very conservative, however, and we posit that future studies should empirically measure EIP under a repeat feeding model. Our findings echo previous work where periods of extensive egg quiescence affected the reproductive success of Wolbachia-infected Ae. aegypti. Additionally, we show that increased biting behavior in association with this infertility in Wolbachia-infected mosquitoes may drive greater vector competence. These relationships require further exploration, given their ability to affect the success of field releases of Wolbachia for human disease reduction in drier climates where longer egg quiescence periods are expected.